An Engineered Superhydrophilic/Superaerophobic Electrocatalyst Composed of the Supported CoMoSx Chalcogel for Overall Water Splitting. Issue 4 (2nd December 2019) - Shan, Xinyao; Liu, Jian; Mu, Haoran; Xiao, Yao; Mei, Bingbao; Liu, Wengang; Lin, Gang; Jiang, Zheng; Wen, Liping; Jiang, Lei
Abstract: The development of high‐efficiency electrocatalysts for large‐scale water splitting is critical but also challenging. In this study, a hierarchical CoMoS x chalcogel was synthesized on a nickel foam (NF) through an in situ metathesis reaction and demonstrated excellent activity and stability in the electrocatalytic hydrogen evolution reaction and oxygen evolution reaction in alkaline media. The high catalytic activity could be ascribed to the abundant active sites/defects in the amorphous framework and promotion of activity through cobalt doping. Furthermore, the superhydrophilicity and superaerophobicity of micro‐/nanostructured CoMoS x /NF promoted mass transfer by facilitating access of electrolytes and ensuring fast release of gas bubbles. By employing CoMoS x /NF as bifunctional electrocatalysts, the overall water splitting device delivered a current density of 500 mA cm −2 at a low voltage of 1.89 V and maintained its activity without decay for 100 h. Abstract : Got to split ! A CoMoS x chalcogel was synthesized in situ on nickel foam (NF) to give superhydrophilic/superaerophobic CoMoS x /NF, which served as a highly efficient catalyst for electrochemical hydrogen evolution and oxygen evolution reactions owing to the enhanced departure of gas bubbles. The overall water splitting device delivered a current density of 500 mA cm −2 at a voltage of 1.89 V and maintained its activity without decay for 100 h.